Społeczne zaplecze systemów totalitarnych - robotnicy wobec władzy komunistycznej w Polsce (1945-1989) - Chumiński, Jędrzej (The social background of totalitarian systems - workpeople in relation to the communist authority, 2006)
The twentieth century passed overshadowed by two powerful totalitarian systems: the communist one and the fascist one. The key problem is the issue of their social background. The article presents the main interpretations explaining the sources of totalitarian temptation, which lured milion of people in the past. Among various explanations the cognitive approach seems to be the most perspective. It stresses intellectual abilities and the broadmindedness of an individual as the basic factors making people immune to the agitation of radical groups. In this context we have analysed the biosocial characteristics of workpeople who supported the totalitarian regime in Poland after World War II. The data we have obtained prove that among the members of the communist party, socially weak circles constituted a much higher percentage than among other working groups. Their level of education was lower, they originally came from villages and small towns more frequently. The percentage of the party members where also higher in the branches dominated by women and in factories where the staff had undergone break-up and disintegration. In this context, the following hypothesis seems well-disintegration. In this context, the following hypothesis seems well-grounded: the workpeople’s membership of PPR and later on their support for the totalitarian authority, resulted not so much from the identification with the ideology and the goals of the regime, but more from the intensity of authoritarian attitudes among them. This conclusion proves the relevancy of the cognitive approach. Therefore, in the light of these theories, the support for radical and antidemocratic paries was supplied mainly by social circles which were unprivileged both with respect to their low educational level and also financial situation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 75-103